The Shengold Jewish Encyclopedia - Schreiber, Mordecai (Lanham : Taylor Trade Pub., 2011)
First published in 1957, this one-volume source for everything Jewish has delighted and instructed several generations in the English-speaking Jewish world. Fully updated through 2007, it provides snapshots and in-depth entries on every important Jewish personality, place, concept, event and value in Israel, the United States, and all other parts of the world.
The Shengold Jewish Encyclopedia; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; R; S; T; U; V; W; Y; Z.
Description based on print version record.
Keywords: Jews -- Encyclopedias; Judaism -- Encyclopedias; HISTORY / World; Electronic books